Development of comfort instrument in breast cancer patients: mixed methods study - Purwati, Yuni; Kustiningsih, Kustiningsih (International Journal of Public Health Science (IJPHS), 2023)
The discomfort in breast cancer patients can lead to depression and the desire to die early. The nurses need to know the patient's discomfort as a basis for providing interventions. Previous studies reported that there is no valid and reliable breast cancer comfort assessment instrument applied in Indonesia. This study aimed to produce a valid and reliable comfort assessment instrument for breast cancer patients. This research used mixed-methods; the qualitative stage started with in-depth interviews with five participants completed with Colaizzi analysis and after that a comfort instrument was developed. The instrument development results were tested for the reliability and validity by assessing the content validity index (CVI), Product Moment validity, and Cronbach's alpha reliability on 100 respondents which were selected by purposive sampling. The qualitative study found five basic themes of comfort assessment: physiological comfort, psycho-spiritual, environmental, socio-cultural, and economic. The total of 30 questionnaire items were produced. Product moment test, results of 29 items r count: 0.361 and Cronbach's alpha test results of 0.915. There were 29 items of instruments for assessing the comfort of breast cancer patients that were valid and reliable that can be applied in Indonesia